Homeownership, Community Interactions, and Segregation - Hoff, Karla; Sen, Arijit (World Bank, Washington, D.C., 2013)
The authors consider a multi-community city where community quality is linked to residents' civic efforts, such as being proactive in preventing crime and ensuring the quality of publicly provided goods. Homeownership increases incentives for such efforts, but credit market imperfections force the poor to rent. Within-community externalities can lead to segregated cities-with the rich living with the rich in healthy homeowner communities, and the poor living with the poor in dysfunctional renter communities. The pattern of tenure segregation across communities in the United States accords well with the study's prediction. The authors analyze alternative tax-subsidy policies to alleviate inefficiencies in the housing market and identify the winners and losers under such policies.